Penerapan Metode Demonstrasi dalam Meningkatkan Hasil Belajar Bola Volly pada Siswa Kelas IX.C SMP Negeri 11 Mataram - Saing, Muhammad (Lembaga Yasin AlSys, 2023)
This study aims to determine the Application of the Demonstration Method in Improving the Learning Outcomes of Volleyball Class IX.C Students of SMPN 11 Mataram Odd Semester 2022/2023 Academic Year. The research subjects were class IX.C students of SMPN 11 Mataram for the 2022/2023 academic year, which consisted of 30 students and consisted of 14 male students and 16 female students. The design of this research was classroom action research which was carried out in 2 cycles, each cycle consisting of four stages, namely planning, action, observation/evaluation, and reflection. Data about learning activities were collected using observation sheets, while data about learning outcomes were collected using observation sheets and tests. The data obtained were analyzed using quantitative descriptive statistical analysis methods. Application of the Demonstration Method in Improving Volleyball Learning Outcomes in PJOK Lessons for Class IX.C Students of SMPN 11 Mataram Odd Semester 2022/2023 Academic Year. In class action research (PTK) this was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase student learning completeness in a classical manner, namely in cycle I by 76%, it could increase to 100% in cycle II. The results of this classroom action research show that learning by applying the demonstration method can improve volleyball learning outcomes in PJOK lessons for Class IX.C Students of SMPN 11 Mataram Odd Semester 2022/2023 Academic Year.